Enhancing Digital Literacy and Language Rhetoric among School Leavers: Rethinking Tanzania’s Basic Education Language Curriculum - Philpo John (Indonesian Educational Research Journal, 2024)
This study assessed the language curriculum implemented for basic education in Tanzania on the adequacy of the digitally-enhanced language competences needed in the world of work inspired by digital era. It argues that although language curriculum has been recently changed to respond to the needs of the competence-based language teaching approach, yet the school leavers from basic education in Tanzania not only are unable to sufficiently demonstrate the curriculum target languages proficiency in various communicative situations but also, they do not live the digital citizenship. Using findings from the narrative literature review, the study has shown that, digital literacy, media literacy, job market rhetoric tourism language, and trade and commerce language skills are not adequately integrated in the language curriculum implemented for basic education in Tanzania. Since the reform seemingly show to have been informed by the social efficiency and learner-centered curriculum ideologies, these job-competitive skills have to be at the centre of the language curriculum for basic education to help the school leavers overcome digitally-enhanced communicative challenges of the contemporary world of work. A job-seeker needs to demonstrate the target language proficiency required and its rhetoric so as to deliver services as expected at work. The findings of this study have implications for language curriculum development and policy-making in the country.